2006
DOI: 10.1002/ajim.20373
|View full text |Cite
|
Sign up to set email alerts
|

Long working hours, safety, and health: Toward a national research agenda

Abstract: A framework is proposed for long work hours, including determinants, outcomes, and moderating factors of long work hours, suggesting that studies need to include more clear and complete descriptions of work schedules, worker characteristics, and the work environment, and need to consider a wider range of possible health, safety, social and economic outcomes for workers, families, employers, and the community. Additional studies are needed on vulnerable employee groups and those critical to public safety. More … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
193
2
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 190 publications
(207 citation statements)
references
References 61 publications
8
193
2
4
Order By: Relevance
“…This study shows the risk factors of nosocomial skin infection was not statistically significant,disagree with study done in Kampala, Uganda [18].…”
Section: Discussion:-contrasting
confidence: 99%
“…This study shows the risk factors of nosocomial skin infection was not statistically significant,disagree with study done in Kampala, Uganda [18].…”
Section: Discussion:-contrasting
confidence: 99%
“…However, although several reviews of this field exist (5,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), the few systematic quantifications of the evidence have been based on published cross-sectional (18,19,25) or published longitudinal studies (26). Given the potential publication bias in studies based on published data (27), an individual-participant metaanalysis of unpublished data would provide important complementary evidence to evaluate the effect of long working hours on mental health.…”
mentioning
confidence: 99%
“…Studies have suggested that acclimation to cold environments can moderate response to cold stress, but prior experience was not indicative of subjective or physiological cold tolerance [32,37]. These findings should be considered when addressing occupational health policies within the tourism industry [23]. …”
Section: Resultsmentioning
confidence: 99%
“…mornings and evenings) [21,22]. Moreover, these environmentally stressful expeditions may last for up to 5-hours and offer little to no shelter from the elements during that time, compounding stress with duration [23]. As a result, the individuals with the most responsibility are also the most likely to have attentional and decision-making impairments.…”
Section: Introductionmentioning
confidence: 99%